The Ants Panic: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This story depicts a colony of ants facing a sudden crisis that disrupts their usual routine. As they panic, they learn the importance of teamwork, communication, and staying calm in challenging situations. Through their collective efforts, they find solutions and strengthen their bonds, teaching young readers the value of cooperation and resilience in overcoming obstacles.